(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
We use three different results of the averaging theory of first order for studying the existence of new periodic solutions in the two Duffing differential equations y+ a y= b t and y+a y-c y^3=bt, where a, b and c are real parameters.